REVEALING THE CLASSIFICATION OF IDIOMS AND THE TRANSLATION STRATEGIES FROM ENGLISH INTO INDONESIAN IN “THE RECRUIT” SERIES MOVIE - Sunarti Desrieny Tambunan (Asosiasi Dosen Muda Indonesia, 2023)
All languages have idioms. Idioms define as phrases or chunks which are identified as fixed expressions with a non-literal interpretation. In addition to its non-literal interpretation, some strategies are provided in order to be successfully render the messages into a target language. Thus, this research focuses on revealing (1) the classification of idioms proposed by Glucksberg (2001) and (2) the translation strategies of the idioms proposed by Baker (2018) from English into Indonesian in a series movie entitled “The Recruit” with 8 episodes. To reach the objectives, qualitative descriptive method is applied. The results show that there are 37 idioms found in 8 episodes. The revealing consists of 7 non-compositional idioms, 21 compositional transparent idioms, 5 compositional opaque idioms, and 4 quasi-metaphorical idioms are found. Further, the translation strategies used by the subtitler to translate the idioms from English into Indonesian based on Baker (2018) reveal that two (2) data that are translated using the strategy to translate the English idioms into idioms in Indonesian and 30 data that are translated using the paraphrase strategy from English into Indonesian. Moreover, there are five (5) idioms that are translated literally.